PERCEIVED BURDEN AND ITS EFFECT ON QUALITY OF LIFE IN CAREGIVERS OF CHILDREN WITH AUTISM SPECTRUM DISORDER - Vikram Arun A, R.T. Kannapiran, Venkata Sai Ram Maddineni (South Eastern European Journal of Public Health, 2025)
Background: Caregivers of children with Autism Spectrum Disorder (ASD) often experience significant physical, emotional, and psychological burdens due to the nature of the condition. These burdens can profoundly affect their quality of life (QoL), which in turn can impact their ability to provide optimal care. This study aimed to assess the caregiver burden and its relationship with QoL among caregivers of children with ASD. Materials and Methods: A cross-sectional study was conducted involving 100 primary caregivers of children diagnosed with ASD, aged 3-18 years. The Zarit Burden Interview (ZBI) was used to assess caregiver burden, while the World Health Organization Quality of Life (WHOQOL-BREF) questionnaire was used to evaluate QoL across four domains: physical health, psychological health, social relationships, and environmental health. Statistical analysis was performed using Pearson’s correlation and regression analysis to determine the association between caregiver burden and QoL. Results: The study found that the majority of caregivers experienced moderate to high levels of burden. A significant negative correlation was observed between caregiver burden and all QoL domains (p < 0.05). The strongest correlation was found in the social relationships domain (r = -0.61, p < 0.001). Regression analysis revealed that factors such as higher caregiver burden, unemployment, and lower educational levels were predictors of poorer QoL. Conclusion: The findings highlight the substantial burden faced by caregivers of children with ASD and its detrimental effect on their quality of life. Interventions aimed at reducing caregiver burden, such as mental health support, respite care, and community-based support programs, are crucial. Policies to address these needs could significantly improve both the caregivers’ well-being and the care provided to children with ASD.